Gambaran Cinta Penyandang Tuna Netra Dalam Prespektif Islam Di Slb A Lima Puluh Kota - Romadoni, Musliha (Batanang : Jurnal Psikologi, 2022)
This study aims to find out the description of the love of blind people in Islamic Perspective at SLB A Lima Puluh Kota, how blind people solve problems with their partners, and how blind people communicate through social media. This type of qualitative descriptive research. The results showed that: (1) the picture of love for blind people in an Islamic perspective in SLB A, Lima Puluh Kota Regency, it was found that two blind people (PR) had two aspects of love, while one other person (LK) had these three aspects. From an Islamic perspective, love in the form of courtship is included in adultery according to the verse of the Koran, namely Surah AlIsra verse 32. (2) the way blind people solve problems with their partners uses a Win-win strategy. (3) the way for blind people to communicate through social media using the default application, namely accessibility and communicating with lilting voices in Islam is prohibited in accordance with the verse of the Qur'an Surah Al-Ahzab verse 32.Keywords: Love Relationship, Blind